Background current elimination in thin layer ion-selective membrane coulometry - Grygolowicz-Pawlak, Ewa; Bakker, Eric (Elsevier, 2010)
A promising method for the elimination of undesired capacitive currents in view of realizing a potentially calibration free coulometric ion detection system is presented. The coulometric cell is composed of a porous polypropylene tube doped with a liquid calcium-selective membrane and a silver/silver chloride wire as an inner electrode, forming a thin layer sample between wire and tubing. The total charge passed through the system during potential controlled electrolysis of the thin layer sample is indeed found to be proportional to the amount of calcium present, but non-Faradaic processes do contribute to the obtained signal. We introduce here a multi-pulse procedure that allows one to perform a second excitation pulse at the same excitation potential after exhaustive ion transfer voltammetry of calcium has taken place. The intercept of the calibration curve after background subtraction is found as 20.6 ± 0.6 μC, significantly lower than the value of 54.1 ± 0.8 μC for the uncorrected curve. Changes in sample temperature (from 23 °C to 38 °C) did equally not affect the background corrected coulometric readings, supporting that the procedure renders the readout principle more robust.